Characterization of the complete chloroplast genome of Melampyrum roseum. Issue 2 (3rd July 2019) - Li, Yong-Chao; Zhou, Xiu-Ren; Yang, Jing; Fu, Qing-Yun
Abstract: In this study, the complete chloroplast (cp) genome of Melampyrum roseum was determined through Illumina sequencing method. The complete cp genome of M. roseum was 143, 896 bp in length and contained a pair of IR regions (25, 210 bp) separated by a small single-copy region (10, 292 bp) and a large single-copy region (83, 184 bp). The cp genome of M. roseum encoded 117 genes including 78 protein-coding genes, 31 tRNA genes, and 8 rRNA genes. The overall GC content of M. roseum cp genome is 38.1%. By phylogenetic analysis using maximum-likelihood (ML) method, M. roseum was placed in Rhinantheae clade as expected.